Efikasi beberapa jenis fungisida nabati untuk mengendalikan penyakit bulai pada tanaman jagung varietas BISI-18 - Ningrum, Anggun Shermila Zahra Candra; Ginting, Cipta; Maryono, Tri; Aeny, Titik Nur; Sudarsono, Hamim; Hariri, Agus Muhammad (Universitas Lampung, 2024)
Downy mildew disease (Maize downy mildew) caused by Peronosclerospora spp. is a major disease in corn that can significantly reduce corn production. An environmentally friendly alternative method to control this disease is the use of botanical fungicides. This study aimed to evaluate the efficacy of botanical fungicides derived from betel leaf extract (Piper betle), Javanese chili leaf extract (Piper retrofractum), and neem leaf extract (Azadirachta indica) in controlling downy mildew disease in BISI-18 corn variety. The research was conducted from January to June 2024. The experimental plots measured 2 x 1.25 m (2.5 m²). Treatments were arranged in a randomized block design (RBD) on a 12 x 9 m plot, consisting of five treatments and six replications (groups). Natural inoculation of the downy mildew pathogen was carried out by placing one symptomatic plant in each experimental plot. Observed variables included incubation period, disease incidence and severity, AUDPC (Area Under Disease Progress Curve), phytochemical analysis, and yield. The results showed that the botanical fungicide from betel leaf extract was the most effective in reducing the intensity of downy mildew, while both betel leaf extract and neem leaf extract were moderately effective in suppressing the AUDPC of the disease. However, all botanical fungicide treatments were ineffective in increasing secondary metabolite content and yield of the BISI-18 corn variety.